2018
DOI: 10.5530/srp.2019.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacy Students’ Clinical Skills using Objective Structured Clinical Examination (OSCE): A Literature Review

Abstract: A sys tematic review of clinical pharmacy assessment articles published from 2003 to 2016 was conducted. The electronic databases used to identify relevant studies were PUBMED, Science Direct, Cochrane Database of Systematic Reviews and Google Scholar. Search terms used were "Pharmacy student*" [MeSH] AND "assessment" [MeSH]) AND "Clinical skills" [MeSH]. The variables coded included characteristics of the assessment (e.g. aim, level, duration, learning and teaching methods), methods and outcomes. The electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Objective structured clinical examination (OSCE) [45,46] An OSCE usually comprises a circuit of short (usually 5-10 min although sometimes up to 15 min) stations, in which each student/trainee is examined on a one-to-one basis with one or two examiner(s) and either real or simulated patients Case-based discussion and Entrustment-based discussions (CBD, EBD) [47,48] A written report, followed by a short oral discussion with the student/trainee. Used to assess pharmacotherapy related cases; in EBD's safety risks are especially important.…”
Section: Assessment Tool Reference Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Objective structured clinical examination (OSCE) [45,46] An OSCE usually comprises a circuit of short (usually 5-10 min although sometimes up to 15 min) stations, in which each student/trainee is examined on a one-to-one basis with one or two examiner(s) and either real or simulated patients Case-based discussion and Entrustment-based discussions (CBD, EBD) [47,48] A written report, followed by a short oral discussion with the student/trainee. Used to assess pharmacotherapy related cases; in EBD's safety risks are especially important.…”
Section: Assessment Tool Reference Descriptionmentioning
confidence: 99%
“…Most of these assessment formats can be adapted to (simulated) learning or training situations at the expense of full authenticity, which makes them suitable for use in earlier stages of student development, e.g., during the master program. The use of Objective structured clinical examinations (OSCE) is relatively well investigated [ 44 , 45 ].…”
Section: Feedback Assessment and Monitoringmentioning
confidence: 99%
“…The OSCE originated in medical education in the 1970s and has become a global gold standard to assess clinical skills, knowledge, and behaviors. Consequently, its use in other healthcare professions, including pharmacy, continues to grow ( Hasan, 2016 , Kristina and Wijoyo, 2018 , Lacy et al, 2019 , Lynga et al, 2019 , Wardman et al, 2017 ). A literature review explored the characteristics of 14 publications of OSCE implemented for pharmacy education, and concluded that OSCE has received significant approval by pharmacy faculties and students all over the world as a reliable and valid tool for competency assessment ( Kristina and Wijoyo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the students preferred OSCE over the other assessment methods. It is a good practice for pharmacy curriculum developers to map the knowledge, skills, and competencies which are assessed by different assessment methods, including the OSCEs, across the pharmacy degree program (Kristina & Wijoyo, 2018). This mapping evidence should then be accessible by the students to demonstrate how OSCEs contribute to their learning journey in the pharmacy school.…”
Section: Osce In Comparison With Other Assessment Methodsmentioning
confidence: 99%